Transitivity Analysis of Newspapers’ Headlines Depicting the Russian Attack on Ukraine - EL FALLAKI, EL HOUSSINE (International Journal of Linguistics and Translation Studies, 2022)
The current study analyzes international newspapers headlines depicting Russia attack on Ukraine. Different newspapers worldwide were chosen to highlight the embedded ideologies by applying Halliday’s transitivity system as a research instrument. The researcher analyzed the lexical choices and the linguistic devices used in headlines to represent Putin and Russia in the war between Russia and Ukraine. He investigated the way language is used in newspapers’ headline to create emotional impacts on the part of the readers and to influence the common public opinion about the crisis. The study highlights the hidden ideologies conveyed through the choice of lexical devices and the way the same event can be represented differently. Key words: transitivity, lexical choice, ideology, representation, public opinion making.